Badlands [videorecording (DVD)] - Malick, Terrence, 1943-; Sheen, Martin; Spacek, Sissy; Oates, Warren, 1928-1982; Almereyda, Michael (Criterion collection, 2013)
Based on the Starkweather-Fugate killing spree of 1958, in which a fifteen-year-old girl and her twenty-five-year-old boyfriend slaughtered her entire family and several others in the Dakota badlands.